Inferior vena cava filters in cancer patients: to filter or not to filter - Hikmat Abdel-Razeq; Asem Mansour; Yousef Ismael; et al (Dove Medical Press, 2011)
Hikmat Abdel-Razeq1, Asem Mansour2, Yousef Ismael1, Hazem Abdulelah11Department of Internal Medicine, 2Department of Radiology, King Hussein Cancer Center, Amman, JordanPurpose: Cancer and its treatment are recognized risk factors for venous thromboembolism (VTE); active cancer accounts for almost 20% of all newly diagnosed VTE. Inferior vena cava (IVC) filters are utilized to provide mechanical thromboprophylaxis to prevent pulmonary embolism (PE) or to avoid bleeding from systemic anticoagulation in high-risk situations. In this report, and utilizing a case study, we will address the appropriate utilization of such filters in cancer patients.Methods: The case of a 43-year-old female patient with rectal cancer, who developed deep vein thrombosis following a complicated medical course, will be presented. The patient was anticoagulated with a low molecular weight heparin, but a few months later and following an episode of bleeding, an IVC filter was planned. Using the PubMed database, articles published in English language addressing issues related to IVC filters in cancer patients were accessed and will be presented.Results: Many recent studies questioned the need to insert IVC filters in advanced-stage cancer patients, particularly those whose anticipated survival is short and prevention of PE may be of little clinical benefit and could be a poor utilization of resources.Conclusion: Systemic anticoagulation can be safely offered for the majority of cancer patients. When the risk of bleeding or pulmonary embolism is high, IVC filters can be utilized. However, placement of such filters should take into consideration the stage of disease and life expectancy of such patients.Keywords: anticoagulation, bleeding, chemotherapy